Evaluation of the Soil–Water Retention Curve of Arsenic-Contaminated Soil by the Filter Paper Method - Ismael Vásquez-Nogal; Christian E. Hernández-Mendoza (Applied Sciences, 2022)
Arsenic is a metalloid frequently found in contaminated sites due to its easy mobilization in the environment. This has attracted the researchers who have studied this phenomenon from an environmental engineering perspective. Although there is evidence indicating that soil contamination impacts its geotechnical behavior, there is no available information about the changes in the soil’s suction after its contamination. The objective of this paper was to evaluate the soil–water retention curve of arsenic-contaminated soil. An unsaturated soil sample was contaminated with arsenic at two different concentrations and a filter paper calibration curve was developed for each contaminant concentration. Soil contamination decreased the BET area and increased its pore sizes. At a saturation rate of 0.8, the matric suction of the contaminated soils decreased (from 1681 kPa to 260 kPa), while the osmotic suction increased (from 23 kPa to 530 kPa), compared with the natural soil’s condition. Furthermore, the soil’s suction values obtained with the ASTM D5298 calibration curve were higher than those obtained using the calibration curve developed for the contaminated state. Thus, to avoid misunderstanding the mechanical behavior of the unsaturated soils under contaminated conditions, the osmotic suction should be considered and evaluated with the corresponding calibration curve.